Generalized static electromagnetic fields in Brans-Dicke theory - Singh T.; Rai L.N. (My University, 2025)
A general class of static, axially symmetric solutions of the Brans-Dicke-Maxwell equations is obtained under the assumption - r 2·grr = gtt·g φφ·gzz. These solutions have been subjected to conformal transformation and they are found to be new solutions of the static, axially symmetric Einstein-Maxwell scalar fields. We have also developed a more general set of solutions under the unit transformations given by Morganstern. © 1979 American Institute of Physics.